A Bibliometric Analysis on Muslim-Friendly Tourism Research Using VOSviewer - Rasuman, Mohammad A; Saeed, Abdulmalek Marwan M. (Future Science / FSH-PH Publications, 2024)
This manuscript focuses on the growth of Muslim-friendly tourism through a thorough bibliometric analysis, addressing the emerging subject in this field. It starts by outlining how important it is to accommodate Muslim tourists in the global tourism scene. Methodologically, the analysis utilized VOSviewer software, and data was collected from national and international publications covering the years 2018–2023 using the Publish or Perish application. The results provide insights into the changing themes and patterns in Muslim-friendly tourism, guiding future research and advancement. Based on the results, the number of studies related to Muslim-friendly tourism in 2018 was low, with only 2 related studies. In the following years, this topic became significantly popular, with a number of studies conducted by various researchers, particularly in 2021 and 2023. In 2019, there was a significant increase, with 9 related studies. In 2021 and 2023, 22 relevant studies were found. There was also a slight decline in 2020, with 7 studies, and 10 studies in 2022. This data is helpful in evaluating the novelty of topics related to Muslim-friendly tourism.